Informal Economy: Conceptual Description And Analysis Of The Impact On Labor Informality (Journal of Namibian Studies : History Politics Culture, 2022)
The purpose of this research is to analyze the empirical studies of the informal economy and its incidence on informal employment in emerging regions. The systematic documentary review method was applied using the high-impact scientific databases Scopus and Science Direct, for the time interval from 2010 to 2023, obtaining a record of 10,645 articles, which was reduced to 43 documents, as a result of the application of the inclusion and exclusion criteria, it was determined in Latin America that in 90% of emerging countries with low and middle income, the female gender has a greater propensity to fall into informality (23.5%), compared to men, given the limitations to access to education and geographical location in rural areas. It is concluded that informality is strongly linked to the lack of opportunities and the structural dimensions of social inequity identified in the social and economic conditionalities in the territories, which are more pronounced among women.